Anti-neuroinflammatory Activity of Elephantopus scaber L. via Activation of Nrf2/HO-1 Signaling and Inhibition of p38 MAPK Pathway in LPS-Induced Microglia BV-2 Cells - Chan, Chim-Kei; Tan, Loh Teng-Hern; Andy, Shathiswaran N.; Kamarudin, Muhamad Noor Alfarizal; Goh, Bey-Hing; Kadir, Habsah Abdul (Frontiers in Pharmacology, 2017)
Elephantopus scaber has been traditionally utilized as a folkloric medicine and scientifically shown to exhibit anti-inflammatory activities in various in vivo inflammatory models. Given the lack of study on the effect of E. scaber in neuroinflammation, this study aimed to investigate the anti-neuroinflammatory effect and the underlying mechanisms of ethyl acetate fraction from the leaves of E. scaber (ESEAF) on the release of pro-inflammatory mediators in lipopolysaccharide (LPS)-induced microglia cells (BV-2). Present findings showed that ESEAF markedly attenuated the translocation of NF-κB to nucleus concomitantly with the significant mitigation on the LPS-induced production of NO, iNOS, COX-2, PGE2, IL-1β and TNF-α. These inflammatory responses were reduced via the inhibition of p38. Besides, ESEAF was shown to possess antioxidant activities evident by the DPPH and SOD scavenging activities. The intracellular catalase enzyme activity was enhanced by ESEAF in the LPS-stimulated BV-2 cells. Furthermore, the formation of ROS induced by LPS in BV-2 cells was reduced upon the exposure to ESEAF. Intriguingly, the reduction of ROS was found in concerted with the activation of Nrf2 and HO-1. It is conceivable that the activation promotes the scavenging power of antioxidant enzymes as well as to ameliorate the inflammatory response in LPS-stimulated BV-2 cells. Finally, the safety profile analysis through oral administration of ESEAF at 2000mg/kg did not result in any mortalities, adverse effects nor histopathologic abnormalities of organs in mice. Taken altogether, the cumulative findings suggested that ESEAF holds the potential to develop as nutraceutical for the intervention of neuroinflammatory disorders.